Shock compression and recovery of microorganism-loaded broths and an emulsion - Hazell, Paul J.; Groves, Kathy H. M.; Stennett, Christopher; Beveridge, C. (American Institute of Physics (AIP), 2009)
The microorganisms Escherichia coli, Enterococcus faecalis and Zygosaccharomyces bailii and an oil-based emulsion, have been subjected to shock compression using the flyer-plate technique to initial pressures of 0.8 GPa (in the suspension). In each experiment, a stainless steel capsule was used to contain the broths and allow for recovery without contamination. Where cavitation was mostly suppressed by virtue of simultaneous shock and dynamic compression, no kill was observed. By introducing an air gap behind the suspension, limited kill was measured in the yeast. Results also suggest that stable emulsification occurs in coarse oil- based emulsions that are subjected to shock.
Shock Compression of Condensed Matter 2009: Proceedings of the American Physical Society Topical Group on Shock Compression of Condensed Matter, 28 June -3 July 2009, Nashville, TN, USA
Keywords: Shock compression; microorganisms, yeast, capsule design